Travel demand estimation through corridor level analysis for hyderabad metro rail - Shekar Lokku, Prashanth; Prasad, Csrk (International Journal of Engineering and Technology, 2018)
Urbanisation around the world is occurring in a rapid manner. Due to which peoplesâ€™ lives are in measurable situation like damaging the environment via increase in usage of private vehicles. In this line, transportation engineering plays a vital role in terms of sustainable development. Sustainability is the term used for balancing the three main components like social, environment and economic; not to trouble much of natural resources so as to preserve them for the future generations. To address the problems related to the transportation like traffic congestion, increase in pollution etc., Mass Rapid Transit System (MRTS) is the best alternative. To plan the MRTS in urban areas, it is necessary to estimate the travel demand, so as to fulfil the financial viability criteria.Corridor level analysis is performed to estimate the travel demand for Hyderabad Metro Rail, India. Multinomial Logit model (ULOGIT) is used to obtain the probability of MRT desired upon various modes. The results revealed that there would be adequate demand for the proposed MRT if the MRT could have double fare than that of bus fare and has half of the travel time to that of the current bus.Â Â